(untitled) - C St J Yales (New York, 1992)
The book deals with the general areas of restaurant, bars, food etc and includes menus, wine lists, ordeling, silver service and cookery terms.
Keywords: english language - spoken english,english language - textbooks for foreign speakers,test of english as a foreign language - study guides